A Comparative Study of Electrocardiographic and Echocardiographic Evidence of Left ventricular Hypertrophy - Mia, M Razzak; Ekram, ARM Saifuddin; Haque, M Azizul; Raisuddin, M (TAJ: Journal of Teachers Association, 2009)
This study was carried out in medicine and cardiology indoor of Rajshahi Medical College Hospital from November 2004 to October 2005. 100 cases were selected for this study in random manner. Sensitivity of ECG to diagnose LVH was found to be 87.5%, and specificity was only 50%. ECG is relatively insensitive and can't accurately identify the severity of LVH. doi: 10.3329/taj.v20i1.3085 TAJ 2007; 20(1): 24-27